A state-of-the-art differential evolution algorithm for parameter estimation of solar photovoltaic models. (15th February 2021) - Gao, Shangce; Wang, Kaiyu; Tao, Sichen; Jin, Ting; Dai, Hongwei; Cheng, Jiujun
Highlights: A directional permutation differential evolution algorithm (DPDE) is proposed. DPDE is applied on parameter estimation of solar photovoltaic (PV) models. Six groups of PV experiments are conducted. Extensive performance comparison with other fifteen algorithms is done. Results show that DPDE outperforms other algorithms in terms of solution accuracy. Abstract: Photovoltaic (PV) generation systems are vital to the utilization of the sustainable and pollution-free solar energy. However, the parameter estimation of PV systems remains very challenging due to its inherent nonlinear, multi-variable, and multi-modal characteristics. In this paper, we propose a state-of-the-art optimization method, namely, directional permutation differential evolution algorithm (DPDE), to tackle the parameter estimation of several kinds of solar PV models. By fully utilizing the information arisen from the search population and the direction of differential vectors, DPDE can possess a strong global exploration ability of jumping out of the local optima. To verify the performance of DPDE, six groups of experiments based on single, double, triple diode models and PV module models are conducted. Extensive comparative results between DPDE and other fifteen representative algorithms show that DPDE outperforms its peers in terms of the solution accuracy. Additionally, statistical results based on Wilcoxon rank-sum and Friedman tests indicate that DPDE is the most robust and best-performing algorithm for the parameter estimation of PV systems.